2017
DOI: 10.1007/s00401-017-1792-9
|View full text |Cite
|
Sign up to set email alerts
|

Spread of aggregates after olfactory bulb injection of α-synuclein fibrils is associated with early neuronal loss and is reduced long term

Abstract: Parkinson’s disease is characterized by degeneration of substantia nigra dopamine neurons and by intraneuronal aggregates, primarily composed of misfolded α-synuclein. The α-synuclein aggregates in Parkinson’s patients are suggested to first appear in the olfactory bulb and enteric nerves and then propagate, following a stereotypic pattern, via neural pathways to numerous regions across the brain. We recently demonstrated that after injection of either mouse or human α-synuclein fibrils into the olfactory bulb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
183
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(222 citation statements)
references
References 75 publications
35
183
2
2
Order By: Relevance
“…In the latter 21.5‐month‐old males, fibril infusions elicited mild loss of NeuN + neurons in the AON. In contrast, Rey and colleagues achieved severe cell loss in this structure 6 months after fibril infusions in the OB of young C57 mice , perhaps because of differences in fibril sonication protocols or mouse strain; they employed C57 mice, whereas we examined CD1 mice.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the latter 21.5‐month‐old males, fibril infusions elicited mild loss of NeuN + neurons in the AON. In contrast, Rey and colleagues achieved severe cell loss in this structure 6 months after fibril infusions in the OB of young C57 mice , perhaps because of differences in fibril sonication protocols or mouse strain; they employed C57 mice, whereas we examined CD1 mice.…”
Section: Discussionsupporting
confidence: 80%
“…Pinto and colleagues reported that 40% of older adults with complete smell loss were dead within 5 years (compared to only 10% of older adults with intact smell perception), and that smell loss was linked to higher mortality rates than heart failure, stroke, cancer and diabetes . Rey et al did not report an increase in mortality from olfactory‐seeded α‐synucleinopathy, but their mice were 3 months old at the time of fibril injections . In the present study, animals injected at 3 months of age also did not exhibit an increase in mortality, whereas infusions in the 11‐month‐old mice only exerted significant lethal effects by 10.5 months post‐infusion.…”
Section: Discussioncontrasting
confidence: 46%
“…After 12 months, pS129‐positive inclusions were detected throughout the brain in connected areas, including the SNpc. However, there was no further progression of Lewy body‐like pathology at 23 months when pS129 was propagation studied after injecting PFFs into the mouse gastric wall (Rey et al., ; Uemura et al., ). The study demonstrated formation of pS129‐positive aggregates in the dorsal motor nucleus of the vagus nerve, which could be prevented by vagotomy.…”
Section: Alpha‐synuclein Overexpression Modelsmentioning
confidence: 99%
“…A similar model in rats and non‐human primates also only showed minor Lewy body‐like pathology in rats at 1 month, which was gone over time despite persistent pathology in the enteric nervous system. Nor was Lewy body‐like pathology (Rey et al., ; Uemura et al., ) detected in non‐human primates at 12 months, despite extensive spread of α‐synuclein pathology in the enteric nervous system (Manfredsson et al., ).…”
Section: Alpha‐synuclein Overexpression Modelsmentioning
confidence: 99%
“…It has also been suggested that the distinct sequence of clinical features in PDD and DLB may result from pathology originating at different predilection sites, with PD beginning in the motor regions of the brainstem and midbrain, perhaps subsequent to peripheral α‐synucleinopathy, and DLB originating in the olfactory bulb interconnected to cognitive regions of the limbic system and neocortex (Rey et al . ).…”
mentioning
confidence: 97%